Determinants of Family Consent to Tissue Donation - Siminoff, Laura A. (2010)
BACKGROUND: Family consent to tissue donation currently falls well below that for solid organ donation. Moreover, research suggests that Americans have limited understanding of tissue donation, an activity largely overshadowed by the more publicly visible organ donation. This research sought to identify determinants of families’ consent to tissue donation. METHODS: Data collection included a brief, self-administered survey completed by tissue bank staff and telephone interviews with family for a sample of tissue donor-eligible deaths reported to a national sample of 16 United States Tissue banks from 2003 to 2006. Family members (N = 1,418) and tissue bank staff (n = 226) involved in the tissue donation decision participated in the research. RESULTS: The families of 1,015 (71.6%) tissue donor-eligible patients consented to tissue donation; 403 (26.8%) families refused. Results revealed a multitude of associations between study variables and the donation decision. A subsequent multivariable analysis identified determinants of family consent to tissue donation, including the discussion of key donation-related issues during the request (adjusted odds ratio [AOR], 17.22; 95% confidence interval [CI], 11.61–25.54), the quality of communication during the request (AOR, 12.39; CI, 7.76 –20.02), families’ tissue donation attitudes and knowledge (AOR, 10.01; CI, 6.47–15.50), families’ initial reactions to the request (AOR, 7.86; CI, 5.13–12.05), families’ advance notice of the request (AOR, 3.95; CI, 2.41– 6.46), and patient and family sociodemographic characteristics (AOR, 3.32; CI, 2.01–5.48). CONCLUSIONS: Family consent to tissue donation is affected by many of the same variables influencing consent to solid organ donation. Recommendations for practice are provided.